English as Business Lingua Franca: Examining the Use of English in Indonesian Online Business - Sri Wahyuningsih; Firda Ziyana Untsa (ELT-Lectura, 2023)
English has become a global language due to its widespread usage around the world, which has also influenced the business world. The term "English as Business Lingua Franca" refers to the use of English as a communication tool for business purposes. The objective of this study is to describe how Indonesian online businessmen perceive English and examine the impact of using it as a Business Lingua Franca on their businesses. Data were collected through a mixed-method approach, including online questionnaires and semi-structured interviews. The findings suggest that Indonesian online businessmen mainly use English as a marketing tool, and despite the difficulties they face while using it, they rely on it for various business endeavors. The study recommends that employers provide their employees with English courses to improve their communication skills with customers and enhance their business skills. In conclusion, the use of English in business communication is essential and beneficial in Indonesia as it has become a global language.